A study on the impact of job stress towards employee’s job performance in Selangor State Development Corporation (PKNS) / Nur Alia Mohd Sanuri and Nabilah Syafiqah Nordin - Mohd Sanuri, Nur Alia; Nordin, Nabilah Syafiqah (Faculty of Business and Management, 2016)
The high level of stress in organization is a serious problem which can cause a decreasing in job performance and motivation level of employees. In order to retain excellent employees and stimulating them to do their best to perform the job, the researchers are motivated for this study to identify the relationship between job stress (workload, role conflict, inadequate monetary rewards, working environment and management support) and employee’s job performance in PKNS. Also, to identify which dimensions of job stress can affect employees the most in PKNS. A descriptive survey design was adopted for the present study. The study was conducted in PKNS. The researchers relied on the questionnaire as the major instrument in order to gather information from employees. The sample size consists of 116 employees in which samples were selected by simple random sampling. SPSS20.0 statically analysis software was used for reliability analysis, correlation analysis and multiple regression analysis to test the hypothesis. The study findings demonstrated that the rank order of job stress’ factors were workload having first rank, inadequate monetary rewards was ranked second, working environment ranked third, management support ranked fourth and role conflict was having fifth rank. The findings of the study may help to increase employee’s job performance in PKNS and encourage them to stay at their work. This also can avoid high turnover which it can be a wasteful of organization’s human resource.